Treatment of small cell lung carcinoma in association with cryptogenic fibrosing alveolitis. Issue 677 (March 1982) - Lipton, J. R.; Carroll, K.; Mould, J. J.; Winstanley, J.; Thatcher, N.
Abstract : Two patients with small cell bronchogenic carcinoma associated with cryptogenic fibrosing alveolitis are described. Both patients received radiotherapy and i.v. chemotherapy with moderate dose methotrexate (100 mg/m 2 ) and escalating high dose cyclophosphamide (1·5 g, 2·5 g, 3·5 g/m 2 ). Good symptomatic improvement was obtained with concurrent tumour response. No effect upon the alveolitis was observed. The pulmonary toxicity associated with methotrexate, cyclophosphamide chemotherapy and radiotherapy is described. The use of immunosuppressive agents (including cytotoxic drugs) to improve fibrosing alveolitis is also discussed There is no apparent contraindication for intensive antitumour therapy in patients with small cell lung cancer and fibrosing alveolitis.